STILISTIKA DALAM NOVEL PARA PRIYAYI KARYA UMAR KAYAM - Sudiyono, Sudiyono; Priyadi, Agustinus Totok; Salem, Laurensius (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study tries to analyze the stylistics in the novel Para Priyayi by Umar Kayam. To answer this problem, this research uses descriptive research method and a qualitative research form with an objective approach. The research data was collected by using the documentation method through the reading of semiotic models, namely heuristic reading and hermeneutic. The results of the study show the facts about the selection and use of vocabulary in the novel Para Priyayi by Umar Kayam. The uniqueness of the selection and the use of vocabulary is seen in (1) the selection and the use of Javanese language vocabulary, (2) the selection and the use of Dutch vocabulary, (3) the selection and the use of Japanese vocabulary, and (4) the selection and use of greeting. There are particularities in the use of figurative linguistic styles which include the use of expressions, proverbs, images, and figure of speech. The uniqueness or the peculiarities of language use in the Para Priyayi novel are motivated by socio-cultural and educational factors of the writer which is expressed through the description of the story. Keywords: Figurative Language Style, Stile, Stylistics.